Assessing the safety of physician-directed nurse-administered propofol sedation in low-risk patients undergoing endoscopy and colonoscopy - Sathananthan, Dharshan; Young, Edward; Nind, Garry; George, Biju; Ashby, Angelie; Drummond, Sharon; Redel, Kasia; Green, Neville; Singh, Rajvinder (Endoscopy International Open, 2017)
Background and study aims Physician-directed nurse-administered balanced propofol sedation (PhD NAPS) in patients undergoing endoscopy and/or colonoscopy is being increasingly utilized worldwide. However, this method of sedation is not universally employed in Australian hospitals due to concerns surrounding its safety. The aim of this study was to assess the safety of PhD NAPS in low-risk patients undergoing endoscopy and/or colonoscopy. Patients and methods This study was conducted at a single tertiary teaching hospital in Adelaide, Australia. It was a prospective study involving 1000 patients with an ASA score of 1 – 3 presenting with any indication for endoscopy, colonoscopy or both. A total of 981 patients (451 male) with a mean age of 53 years (range: 16 – 87) were recruited from January 2010 to October 2012. 440 endoscopies, 420 colonoscopies, and 121 combined procedures were performed. The intra-procedural adverse events (AEs) were recorded. Results There were no major intra-procedural adverse events. Minor AEs occurred in 6.42 % of patients, and resolved spontaneously or with intravenous fluid boluses in all cases. Conclusion PhD NAPS is safe when the proceduralist and nursing staff are adequately trained and strict patient selection criteria are used.